2015
DOI: 10.1515/acph-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Alginate microspheres obtained by the spray drying technique as mucoadhesive carriers of ranitidine

Abstract: Alginate microspheres obtained by the spray drying technique as mucoadhesive carriers of ranitidineThe present study is aimed at formulation of alginate (ALG) microspheres with ranitidine (RNT) by the spray drying method. Obtained microspheres were characterized for particle size, surface morphology, entrapment efficiency, drug loading, in vitro drug release and zeta potential. Mucoadhesive properties were examined by a texture analyser and three types of adhesive layers -gelatine discs, mucin gel and porcine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Owing to mucoadhesive properties, ALG are regarded as proper polymer excipients to prepare buccal [97][98][99], nasal [100,101], ocular [102,103], and gastrointestinal dosage forms [104][105][106][107][108]. Recently, several studies have shown favourable mucoadhesiveness of ALG-based applications in contact with vaginal mucosa tissue [108,109].…”
Section: General Properties Of Algmentioning
confidence: 99%
“…Owing to mucoadhesive properties, ALG are regarded as proper polymer excipients to prepare buccal [97][98][99], nasal [100,101], ocular [102,103], and gastrointestinal dosage forms [104][105][106][107][108]. Recently, several studies have shown favourable mucoadhesiveness of ALG-based applications in contact with vaginal mucosa tissue [108,109].…”
Section: General Properties Of Algmentioning
confidence: 99%
“…peptides and proteins) (Coppi et al, 2002), A c c e p t e d M a n u s c r i p t small molecules (e.g. ranitidine) (Szekalska et al, 2015) and lipopolysaccharides (Jain et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Mucoadhesive Microsphere of ALG have recently demostrated to be a unique "carrier system" for many pharmaceuticals preparation increasing oral iron bioavailability of many drugs such as metformin, amoxicillin, furosemide, ibuprofen, insulin, acyclovir, captopril, glipizide and dicumarol [9][10][11] resulting in a promising drug delivery system [12].…”
Section: Introductionmentioning
confidence: 99%